Analisis Kemampuan Literasi Media Pada Mahasiswa Konsumtif Fenomena Konten “Racun TikTok” (Penelitian Fenomenologi pada Mahasiswa Telkom University) - Ulya, Humaira Fathya; Anggraini, Clara Novianti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The phenomenon of toxic content on social media, especially TikTok, is in the spotlight because of its potential to influence user perceptions and behavior, especially among students who tend to be consumptive. This research aims to analyze students' media literacy skills related to the phenomenon of toxic content on the TikTok platform, with a focus on the Telkom University student population. This research uses a qualitative method with a phenomenological type of research and uses a constructivist paradigm. Data was collected through in-depth interviews with Telkom University students who actively use TikTok. The analysis was carried out by detailing students' media literacy abilities. It is hoped that the research results will provide an in-depth picture of the extent of Telkom University students' media literacy abilities in dealing with the phenomenon of toxic content on TikTok. The implications of the research findings can be used as a basis for developing media literacy programs in academic environments, so that students can be more aware and critical in consuming content on social media platforms that have a significant impact on everyday life.